Gas exchange and leaf aging in an evergreen oak: causes and consequences for leaf carbon balance and canopy respiration - Rodriguez-Calcerrada, Jesus; Limousin, Jean-Marc; Martin-StPaul, Nicolas K; Jaeger, Carsten; Rambal, Serge (Tree Physiology, 2012)
Leaves of Mediterranean evergreens experience large variations in gas exchange rates over their life span due to aging and seasonally changing environmental conditions. Accounting for the changing respiratory physiology of leaves over time will help improve estimations of leaf and whole-plant carbon balances. Here we examined seasonal variations in light-saturated net CO2 assimilation (Amax), dark respiration (Rd) and the proportional change in Rd per 10 °C change in temperature (Q10 of Rd) in previous-year (PY) and current-year (CY) leaves of the broadleaved evergreen tree Quercus ilex L. Amax and Rd were lower in PY than in CY leaves. Differences in nitrogen between cohorts only partly explained such differences, and rates of Amax and Rd expressed per unit of leaf nitrogen were still significantly different between cohorts. The decline in Amax in PY leaves did not result in the depletion of total non-structural carbohydrates, whose concentration was in fact higher in PY than CY leaves. Leaf-level carbon balance modeled from gas exchange data was positive at all ages. Q10 of Rd did not differ significantly between leaf cohorts; however, failure to account for distinct Rd between cohorts misestimated canopy leaf respiration by 13% across dates when scaling up leaf measurements to the canopy. In conclusion, the decline in Amax in old leaves that are close to or exceed their mean life span does not limit the availability of carbohydrates, which are probably needed to sustain new growth, as well as Rd and nutrient resorption during senescence. Accounting for leaf age as a source of variation of Rd improves the estimation of foliar respiratory carbon release at the stand scale.
10.1093/treephys/tps020
Keywords: carbon budget; ecosystem respiration; leaf life span; resource remobilization; soluble sugars; temperature sensitivity

Internal remobilization of carbohydrates, lipids, nitrogen and phosphorus in the Mediterranean evergreen oak Quercus ilex - Cherbuy, Bénédicte; Joffre, Richard; Gillon, Dominique; Rambal, Serge (Tree Physiology, 2001)
Remobilization of internal resources is an important mechanism enabling plants to be partly independent of external nutrient availability. We assessed resource remobilization during the growing period in woody and foliar tissues of leafy branches of mature evergreen Mediterranean oak (Quercus ilex L.) at three field sites. We compared nonstructural carbohydrates, lipids, nitrogen and phosphorus pools in leaves and stems before bud burst (March) and at the end of the growing period (July). We also experimentally defoliated leafy branches to determine the storage function of old leaves. Changes in pools of carbon compounds in leaves and stems during spring and in response to defoliation indicated that foliar and woody tissues could provide carbon to support shoot growth. Independently of stem age, soluble sugar and lipid pools decreased significantly during spring. Changes in leaf pools between March and July involved all compounds measured except starch and were accompanied by a 5%; decrease in mean leaf biomass. During the same period, 15%; of the nitrogen and 25%; of the phosphorus were removed from leaves. In contrast, woody tissues did not remobilize nitrogen or phosphorus. Our results support earlier hypotheses that leaves of evergreen species have a primary role in resource remobilization.
10.1093/treephys/21.1.9
Keywords: defoliation; Growth; nutrient storage; resource remobilization

Internal remobilization of carbohydrates, lipids, nitrogen and phosphorus in the Mediterranean evergreen oak Quercus ilex - Cherbuy, Bénédicte; Joffre, Richard; Gillon, Dominique; Rambal, Serge (Tree Physiology, 2001)
Remobilization of internal resources is an important mechanism enabling plants to be partly independent of external nutrient availability. We assessed resource remobilization during the growing period in woody and foliar tissues of leafy branches of mature evergreen Mediterranean oak (Quercus ilex L.) at three field sites. We compared nonstructural carbohydrates, lipids, nitrogen and phosphorus pools in leaves and stems before bud burst (March) and at the end of the growing period (July). We also experimentally defoliated leafy branches to determine the storage function of old leaves. Changes in pools of carbon compounds in leaves and stems during spring and in response to defoliation indicated that foliar and woody tissues could provide carbon to support shoot growth. Independently of stem age, soluble sugar and lipid pools decreased significantly during spring. Changes in leaf pools between March and July involved all compounds measured except starch and were accompanied by a 5%; decrease in mean leaf biomass. During the same period, 15%; of the nitrogen and 25%; of the phosphorus were removed from leaves. In contrast, woody tissues did not remobilize nitrogen or phosphorus. Our results support earlier hypotheses that leaves of evergreen species have a primary role in resource remobilization.
10.1093/treephys/21.1.910.1093/treephys/21.1.9
Keywords: defoliation; Growth; nutrient storage; resource remobilization